2020
DOI: 10.1111/liv.14732
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insight into COVID‐19 related liver injury: A note on MBOAT7

Abstract: Sir, with great interest we read the paper by Bianco et al, 1 presenting the association between genetic modifiers of liver injury and outcomes in patients with COVID-19. Whilst Bianco et al 1 showed that the PRS-HFC genetic score does not affect studied phenotypes, they also demonstrated that C3 and AB0 genetic variants are associated with the severity of COVID-19. In this study, we would like to add to these interesting observations and present first data concerning the MBOAT7 polymorphism rs641738 (which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Carriers of the MBOAT7 rs641738 C>T variant displayed more severe liver injury characterized by increased ALP, GGT, ALT, and bilirubin and decreased albumin levels during hospitalization for COVID‐19, as compared to wild type. Moreover, a higher percentage of patients carrying the recessive allele had a more severe respiratory disease 107 …”
Section: Mboat7 Involvement In Extrahepatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carriers of the MBOAT7 rs641738 C>T variant displayed more severe liver injury characterized by increased ALP, GGT, ALT, and bilirubin and decreased albumin levels during hospitalization for COVID‐19, as compared to wild type. Moreover, a higher percentage of patients carrying the recessive allele had a more severe respiratory disease 107 …”
Section: Mboat7 Involvement In Extrahepatic Diseasesmentioning
confidence: 99%
“…Moreover, a higher percentage of patients carrying the recessive allele had a more severe respiratory disease. 107…”
Section: Mboat7 and Covid-19mentioning
confidence: 99%
“…Collectively, these studies suggest that MBOAT7 function is linked to neurodevelopmental issues that likely originate in the central nervous system. Finally, one recent report has also linked MBOAT7 function to coronavirus disease 2019 (COVID-19)-related liver injury (65). Machill et al (65) longitudinally studied a cohort of 44 COVID-19 positive patients and found that the rs641738 T allele was associated with an increased risk of liver injury.…”
Section: Other Links Between Mboat7 Function and Human Diseasementioning
confidence: 99%
“…Finally, one recent report has also linked MBOAT7 function to coronavirus disease 2019 (COVID-19)-related liver injury (65). Machill et al (65) longitudinally studied a cohort of 44 COVID-19 positive patients and found that the rs641738 T allele was associated with an increased risk of liver injury. Collectively, over the past 6 years, numerous human studies have linked genetic variation in the MBOAT7 locus to various diseases, prompting several groups to follow up using animal models to establish causal links to liver disease progression and other related phenotypes.…”
Section: Other Links Between Mboat7 Function and Human Diseasementioning
confidence: 99%
“…55 ABO nonsecretor phenotype, as well as carriers of the MBOAT7 risk allele, were associated with elevated levels of liver enzymes. 56,57 While plasma level of terminal complement complex SC5b-9 was higher in rs11385942 GA carriers than in noncarriers, which was directly associated with the level of AST and gamma-glutamyltransferase (GGT). 58 In some COVID-19 patients who suffered from chronic hepatitis B, liver dysfunction could be caused by reactivation of HBV.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%